Data-driven data transmission of the Internet of things based on sensing spectrum - Xuanheng LI; Yi SUN; Jie WANG; Haixia ZHANG (物联网学报)
Facing the problem of spectrum shortage caused by the mass data,in order to share as a solution,how operators use the sensing spectrum reasonably to transmit data was studied.Considering the limitation of Internet of things(IoT) devices,the ultra-dense cognitive heterogeneous network architecture was designed,based on traffic demand and perception cost,an optimal access control and perception decision method was designed to maximize network utility.Considering the uncertainty of the perceived spectrum,the optimal programming scheme was modeled as a mixed integer stochastic optimization problem,and a data-driven probabilistic solution method based on statistical characteristics was proposed.In the case of unknown probability distribution of available bandwidth,data transmission requirements meeting various service requests were counted.